2011
DOI: 10.1002/pbc.22813
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ewing sarcoma family of tumors with a modified P6 protocol in children and adolescents

Abstract: INTRODUCTIONEwing sarcoma family of tumors (ESFT) is the second most common bone malignancy in children, accounting for approximately 40% of all bone cancers [1]. ESFT is characterized by a specific balanced chromosomal translocation which fuses the amino-terminal domain of the EWSR1 gene or, in rare cases, the TLS/FUS gene, to the DNA-binding domain of one of five ETS genes [2]. The transcripts resulting from these fusion genes can be detected using the reverse transcriptase-polymerase chain reaction (RT-PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Bone marrow mononuclear cell isolation, total RNA extraction and cDNA synthesis were carried out as described [33]. Analysis of PHOX2B mRNA expression was performed following previously reported procedures [34] in a 7000 Sequence Detection System (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow mononuclear cell isolation, total RNA extraction and cDNA synthesis were carried out as described [33]. Analysis of PHOX2B mRNA expression was performed following previously reported procedures [34] in a 7000 Sequence Detection System (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Although 41% of patients had a partial response, 29% experienced progression during this window. All patients then received five‐drug chemotherapy as per the modified P6 protocol 11 followed by local control with surgery and/or radiotherapy. Nonprogressing patients were given up to 12 cycles of GEM/DOC maintenance therapy, and the three‐year event‐free survival for this group was 29%.…”
Section: Introductionmentioning
confidence: 99%
“…Eligible patients were 40 years or younger at enrolment and had diagnosis of ES confirmed by EWSR1 rearrangement by FISH or qRT-PCR analysis. All patients were required to have 2–4 bone marrow (BM) aspirates for centralised study (CdT, Hospital Sant Joan de Déu) of (micro)metastasis according to the methods previously described ( Mora et al , 2011 ). HR-ES was defined as patients presenting with metastasis, primary tumour in the pelvis or axial skeleton, and patients with BM (micro)metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with metastatic disease at diagnosis had a significantly worse prognosis, with 4-year EFS rate of 12.0% and OS of 17.8% ( Kolb et al , 2003 ). In 2001, we modified the original P6 (hereby mP6) protocol ( Mora et al , 2011 ) and the results of a single-institution study with 31 patients showed 4-year EFS rate for non-metastatic cases of 83.0% and OS of 92.0%. Patients with metastatic disease showed 3-year EFS rate of 28.0% and OS of 42.0% ( Mora et al , 2011 ).…”
mentioning
confidence: 99%